Sustainable metal organic framework thin-films for medical sensing applications - Warfsmann, Jan (2019)
We spend more and more time indoors, and the monitoring of the concentration of CO2 and volatile organic compounds (VOCs) is important to maintain comfort, productivity and health. Furthermore, can the long-time exposure to these compounds lead to medical issues like cancer and nerve damage. The accumulation of CO2 and VOC takes place automatically indoors. CO2 is produced by cellular respiration, while VOCs are often outgassed from e.g. paint or furniture. In order to maintain a comfortable indoor atmosphere without wasting energy by wrong heating or ventilation the real-time monitoring of CO2 and VOC concentrations is needed. Long period grating fibres (LPG) are known to be lightweight and low-cost sensors with extreme short response times, possibly in the microsecond scale, but the non-selective response to various stimuli like strain, temperature and refractive index change is problematic for the creation of a reliable real-time sensor system. The use of metal-organic frameworks(MOFs), a new class of hybrid porous materials with tuneable pore size and chemical properties, might be here able to provide selectivity and sensitivity towards specific target compounds as a thin-film coating on the LPG surface. However, MOFs are in general first prepared as powders, often at elevated temperatures and long reaction times. Furthermore is the transformation of a powder synthesis to a thin-film synthesis not trivial. For this work, two promising MOFs, MIL-53(Al) and TIFSIX-3-Ni, have been identified and the possible coating of LPGs was separated into three steps. These are the optimisation of the powder synthesis regarding more sustainable conditions (e.g. shorter reaction times, lower reaction temperature and easier purification of the product), devolving of a thin-film synthesis for glass as support and the application of the most-promising thin-film coating techniques on LPGs. The real-time sensor performance of the MIL-53(Al) and TIFSIX-3-Ni coated LPGs towards CO2 and selected VOCs was tested afterwards. In summary, could be especially the powder synthesis for MIL-53(Al) and TIFSIX-3-Ni in comparison with the literature protocols be improved. It was possible to greatly reduce the reaction time of MIL-53(Al) from 220°C and 72 h to 150°C and 5 h using the low-weight alcohol methanol as solvent. Furthermore, does the MIL-53(Al) derivate prepared in methanol show porosity directly after the synthesis. A common disadvantage of MIL-53(Al) is that normally a time and energy consuming activation process is needed in order to access the internal porosity. For TIFSIX-3-Ni, the yield could be improved and the reaction time reduced in comparison with the literature protocol using N,N-dimethylformamide (DMF) as solvent. For both MIL-53(Al) and TIFSIX-3-Ni new thin-film protocols could be developed for the successful coating of glass surfaces with homogenous and uniform thin-films, but still more research is needed in order to create a reliable and repeatable sensor response of these MOF-coated LPGs.